Peningkatan Efikasi Diri Melalui Penguatan Kepemimpinan Transformasional, Kompetensi Pedagogik Dan Kreativitas Guru - Abidin, Zaenal; Ahmad, Sofyan (Edusifa: Jurnal Pendidikan Islam, 2023)
ABSTRACT This study aims to determine the steps for the formation of religious character in children by Islamic Religious Education teachers at Tarbiyatul Falah Junior High School Ciampea Bogor. This type of research is qualitative descriptive. The subjects in this study were teachers of Islamic Religious Education at Tarbiyatul Falah Middle School, Ciampea Bogor, while the informants in this study were two class VIII students, one teacher at Tarbiyatul Falah Middle School Ciampea Bogor and the principal, Tarbiyatul Falah Junior High School Ciampea Bogor. . The results of the study concluded that: the pattern of religious character formation by Islamic religious education teachers in Tarbiyatul Falah Junior High School students in Ciampea Bogor was quite good because in the Tarbiyatul Falah Junior High School Ciampea Bogor environment, they were very accustomed to discipline, the pattern formed by Islamic Religious Education teachers. The discipline of worship can be applied in direct education for example through teaching and learning activities, example, motivation and supervision in performing worship, through the habituation of dhuha prayers in congregation and midday prayers in congregation and also indirect education by providing discipline to students so that students do not do bad things. in the environment. Keywords: Pattern of students' character formation